Stem cells for stress urinary incontinence: the adipose promise - Roche, Régis; Festy, Franck; Fritel, Xavier (Journal of cellular and molecular medicine, 2010)
• Introduction • The sphincteric complex • Deterioration of the urethral sphincter • Stem cells and their use in the treatment of urinary incontinence • Stem cells from human adipose tissue • Conclusion Stress urinary incontinence (SUI), the most common type of incontinence in women, is a frequent and costly ailment responsible for an alteration in the quality of life. Although medical treatment gives some rather deceiving results, surgical techniques that include colposuspension or tension‐free vaginal tape, employed in cases of urethral support defect, give a 5‐year cure rate of more than 80%. However, these techniques could lead to complications or recurrence of symptoms. Recently, the initiation of urethral cell therapy has been undertaken by doctors and researchers. One principal source of autologous adult stem cells is generally used: muscle precursor cells (MPCs) which are the progenitors of skeletal muscle cells. Recently, a few research groups have shown interest in the MPCs and their potential for the treatment of urinary incontinence. However, using MPCs or fibroblasts isolated from a striated muscle biopsy could be questionable on several points. One of them is the in vitro cultivation of cells, which raises issues over the potential cost of the technique. Besides, numerous studies have shown the multipotent or even the pluripotent nature of stromal vascular fraction (SVF) or adipose‐derived stem cells (ASCs) from adipose tissue. These cells are capable of acquiring in vitro many different phenotypes. Furthermore, recent animal studies have highlighted the potential interest of SVF cells or ASCs in cell therapy, in particular for mesodermal tissue repair and revascularization. Moreover, the potential interest of SVF cells or ASCs for the treatment of urinary incontinence in women is supported by many other characteristics of these cells that are discussed here. Because access to these cells via lipoaspiration is simple, and because they are found in very large numbers in adipose tissue, their future potential as a stem cell reservoir for use in urethral or other types of cell therapy is enormous.